2019
DOI: 10.1111/tan.13628
|View full text |Cite
|
Sign up to set email alerts
|

Soluble HLA‐G levels in seminal plasma are associated with HLA‐G 3′UTR genotypes and haplotypes

Abstract: Soluble HLA‐G (sHLA‐G) levels in human seminal plasma (SP) can be diverse and may affect the establishment of maternal‐fetal tolerance and thereby the outcome of pregnancy. We investigated whether sHLA‐G levels in SP are associated with polymorphisms in the 3′‐untranslated region (UTR) and UTR haplotypes of the HLA‐G gene. Furthermore, we compared the HLA‐G genotype distribution and sHLA‐G levels between men, whose partner experienced unexplained recurrent miscarriage (RM), and controls. Soluble HLA‐G levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(65 reference statements)
2
9
0
Order By: Relevance
“…Haplotypes and diplotypes containing UTR-1 have been associated with high levels of plasma sHLA-G, those containing UTR-5 and UTR-7 with low levels of sHLA-G, and finally, alleles containing UTR-2, UTR-3, UTR-4, and UTR-6 with medium levels of sHLA-G (51). These results were confirmed in other biological fluids as the highest levels of HLA-G in seminal plasma have been detected in the presence of homozygosis for UTR-1 and UTR-3 (52). Our group defined the association of specific UTRs with the expression of HLA-G1 in a specific subset of tolerogenic DC, termed DC-10, inducible in vitro in the presence of IL-10 (53) and present in vivo (54).…”
Section: Association Hla-g Genotype/phenotypesupporting
confidence: 75%
“…Haplotypes and diplotypes containing UTR-1 have been associated with high levels of plasma sHLA-G, those containing UTR-5 and UTR-7 with low levels of sHLA-G, and finally, alleles containing UTR-2, UTR-3, UTR-4, and UTR-6 with medium levels of sHLA-G (51). These results were confirmed in other biological fluids as the highest levels of HLA-G in seminal plasma have been detected in the presence of homozygosis for UTR-1 and UTR-3 (52). Our group defined the association of specific UTRs with the expression of HLA-G1 in a specific subset of tolerogenic DC, termed DC-10, inducible in vitro in the presence of IL-10 (53) and present in vivo (54).…”
Section: Association Hla-g Genotype/phenotypesupporting
confidence: 75%
“…Six studies were excluded from the quantitative meta-analysis [three studies’ data are not available to extract for synthesis ( 19 , 41 , 75 ), three articles reported the polymorphism in only one study thus cannot be synthesized ( 8 , 70 , 76 )]. Finally, four studies were included in the quantitative meta-analysis ( 35 , 77 79 ). The flow diagram of selecting studies for systematic review and meta-analysis is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…HLA-G is oligomorphic and has seven isoforms, of which some are membrane-bound (HLA-G1 to -G4), and others are secreted as a soluble form (sHLA-G5 to -G7) (142). Several polymorphisms in the untranslated region (UTR) of the HLA-G gene have been associated with lower sHLA-G levels in both blood and seminal plasma (143,144). In both PE and RPL, a reduction in serum sHLA-G levels has been observed compared to healthy control women (145)(146)(147)(148).…”
Section: Hla-gmentioning
confidence: 99%